A Multifunctional Dual-Luminescent Polyoxometalate@Metal-Organic Framework EuW10@UiO-67 Composite as Chemical Probe and Temperature Sensor - Salomon, William; Dolbecq, Anne; Roch-Marchal, Catherine; Paille, Grégoire; Dessapt, Rémi; Mialane, Pierre; Serier-Brault, Hélène (Frontiers in Chemistry, 2018)
The luminescent [EuW10O36]9- polyoxometalate has been introduced into the cavities of the highly porous zirconium luminescent metal-organic framework UiO-67 via a direct synthesis approach, affording the EuW10@UiO-67 hybrid. Using a combination of techniques (TGA, BET, Elemental analysis, EDX mapping,…) this new material has been fully characterized, evidencing that it contains only 0.25% in europium and that the polyoxometalate units are located inside the octahedral cavities and not at the surface of the UiO-67 crystallites. Despite the low amount of europium, it is shown that EuW10@UiO-67 acts as a solid-state luminescent sensor for the detection of amino-acids, the growth of the emission intensity globally following the growth of the amino-acid pKa. In addition, EuW10@UiO-67 acts as a sensor for the detection of metallic cations, with a high sensitivity for Fe3+. Noticeably, the recyclability of the reported material has been established. Finally, it is shown that the dual-luminescent EuW10@UiO-67 material behave as a self-calibrated-ratiometric thermometer in the physiological range.